Islamic Art Aesthetics and Modern Philosophy - Al Asqha, Shatha Ibrahim (جمعية إمسيا التربية عن طريق الفن, 2021)
The aim of the current research is to reveal the ideological map of the aesthetic of Islamic arts, And find out whether the philosophy of thought only social and religious in the Islamic civilization and the role of effective in the formation of JAMA mechanisms of Islamic art ,by identifying the concept of ideology in aesthetic Islamic arts ,all the way to learn about the ideological aesthetic philosophy of the arts usage and modern philosophy affecting concepts and developed education to an enterprise community. The study results to a group of them that's for the arts of civilization illiterate ideological format singularly represents the Culture of Muslim community and social idea. The study came out with a number of recommendations, including the need to pay attention to the cultural heritage of Islamic arts through a number of different fields. And the importance of increasing scientific research that focuses on the aesthetics of Islamic arts.
Keywords: الحضارة الإسلامية -- الفلسفة الجمالية -- الفنون الإسلامية -- التراث الثقافي